A Robust Technique for Unambiguous BOC Tracking. Issue 3 (15th September 2014) - Wendel, J.; Schubert, F. M.; Hager, S.
ABSTRACT The GPS M‐Code, Galileo PRS Service, and Galileo Open Service on E1 use a Binary Offset Carrier modulation. The autocorrelation function of a BOC signal has multiple peaks. The main peak of the ACF is much narrower than the peak of the corresponding BPSK signal, which offers the potential for increased tracking accuracy and better multipath resistance. On the other hand, a tracking loop can lock to a side peak of the correlation function instead of the main peak, leading to systematic errors in the pseudorange measurements. In this paper, a new approach for tracking BOC signals is proposed: Ambiguous, accurate delay estimates and unambiguous, less accurate delay estimates are used to calculate a float position solution, and float sub‐carrier ambiguities. Then, the LAMBDA method – typically used to fix the integer ambiguities of carrier phase measurements – is used to fix the sub‐carrier ambiguities, which are then used to calculate the final position solution. First simulation results illustrate the potential of this technique. Copyright © 2014 Institute of Navigation.